TERRORIST ORGANIZATIONS AND SUICIDE ATTACKS (Heritage, 2022)
The terrorist organizations, of course, are not the first organized terrorist group that humanity encountered. The origin of organized terrorist activities, as it is known, is in the distant past. They also will not be the last, because the conditions, which have direct, influence on organization like this one, such as political and economic crises, unfortunately will be in a future inherent in many countries the world.Some terrorist organizations and other similar entities that are using suicide terrorism while planning and organizing suicide attacks using approach with great seriousness and developing special suicide tactics. Thereby they listed suicide terrorism as a special form of fighting with big importance.
Keywords: terrorism, terrorist organizations, suicide attacks